To Evaluate Quality of Cardiopulmonary Resuscitation (CPR) Performed At Scene and During Transport After Out-of-Hospital Cardiac Arrest: A Crossover Trial - Maya Almutairi; Rahaf Margushi; Shahad Alotaibi; Khadijah Banjar; Adel Alanazi; Sharafaldeen Bin Nafisah; Bandr Mzahim (The Journal of Medicine, Law & Public Health)
Background: High-quality cardiopulmonary resuscitation (CPR) is essential to improve survival rates in out-of-hospital cardiac arrest. Previous research suggests that the quality of CPR may decline during ambulance transport.